Capital adequacy and allocation for a property and casualty insurer in Singapore : a comparison between dynamic financial analysis (DFA) model and risk based capital (RBC) requirements. - Cheah, Yen Seng. (2010)
This paper attempts to assess the capital adequacy level of a hypothetical property and casualty (P&C) insurer in Singapore using the existing Risk Based Capital (RBC) framework. Alternatively, we adopt an internal model of Dynamic Financial Analysis (DFA) in modelling the capital adequacy requirement and compare the results of both approaches using a coherent risk measure of Tail Conditional Expectation (TCE). We find that by using DFA model, the capital adequacy requirement of the hypothetical insurer is smaller than that of the RBC framework, which reflects on the conservative approach of Singapore's RBC calculation. Subsequently, this paper discusses the differences in the capital allocation on five lines of business using these two approaches. Consideration has been given on the appropriateness of capital allocation method, in which, the Shapley value from game theory has been chosen. Concluding remarks are made at the end of the paper with suggestions of possible future research.